A New Foundation Model for Dynamic Analysis of Beams on Nonlinear Foundation Subjected to a Moving Mass. (2016) - Nguyen, T.P.; Pham, D.T.; Hoang, P.H.
Abstract: This paper proposes a new foundation model for dynamic analysis of beam on nonlinear foundation subjected to a moving mass. This model includes the linear and nonlinear Winkler parameters, the linear Pasternak foundation parameter, viscous damping and special consideration of the influence of a foundation mass parameter. The governing equation of motion of the system is formulated by finite element method and dynamic balance of principle and solved by the Newmark method in the time domain. The influences of foundation parameters on dynamic responses of the beam are investigated.